Frequency of central lesions in polyneuropathy associated with IgM monoclonal gammopathy: an MRI, neurophysiological and immunochemical study. Issue 2 (February 1992) - Léger, J M; Younes-Chennoufi, A B; Zuber, M; Bouche, P; Jauberteau, M O; Dormont, D; Danon, F; Baumann, N; Brunet, P
Abstract : CNS lesions were studied in polyneuropathy associated with IgM monoclonal gammopathy. Eleven out of 12 patients with IgM MGUS and one patient with Waldenstrom's disease had clinical and electrophysiological features indicating a demyelinating polyneuropathy. MRI showed CNS white matter lesions in two cases. Antibodies reacting against glycolipids present in CNS white matter were present in five cases, two of which had abnormal MRI. Central conduction times cortex-C7, obtained by magnetic stimulation, were prolonged in 3/8 patients, of which two patients had anti-CNS glycolipid antibodies.